(untitled) (Journal of Economic Research & Business Administration, 2016)
The tax system is the main instrument of economic regulation, priori tizing social and economic development. State, wisely using the tools of the tax mechanism, changing tax policy, based on the priorities of eco nomic development, has the opportunity, how to encourage economic growth, and keep it. State tax regulation affects the formation of a favor able business – climate and creates opportunities for innovation. The Government of the Republic of Kazakhstan constantly comple ments, corrects the tax legislation in order to create a tax system of the international level. Changes in tax laws mainly related to the following areas: a revision of tax rates and tax benefits, changes in the number and types of taxes and other obligatory payments to the budget, the adjustment of the individual parameters of tax control, etc. However, the control system of the tax process virtually unchanged. It is well known that the tax system – an essential element of market rela tions, and a lot of it depends on the success of economic reforms in the country.